Hubungan Pengetahuan dan Perilaku Terhadap Pencegahan Penularan Penyakit Kusta di Wilayah Kerja Puskesmas Tempiral Tahun 2021 - Apria Wilinda Sumantri (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Leprosy, by most people better known as leprosy (leprosy), is still a disease that is feared by the public, even by some health workers. So far, the community has developed a stigma that leprosy is a disease of God's curse, a hereditary disease or because of occult sciences that are difficult to cure or even cannot be cured, are considered shameful and cause disgrace to the family..In general, the purpose of the research is to know it the relationship of knowledge and behavior toward the prevention of the transmission of leprosy in the work area of the Puskesmas Tempiral in 2021. This study includes research that uses quantitative correlation methods with a Cross Sectional approach and the number of samples is 30 people. The variables studied were presented in the form of a frequency distribution table and tested with univariate and bivariate analysis, namely by using demographic data instruments, knowledge questionnaires and behavioral questionnaires on the prevention of leprosy transmission and questionnaires on prevention of leprosy transmission. The results of the chi square test get a p value of 0.000 which means that there isit the relationship of knowledge and behavior toward the prevention of the transmission of leprosy in the work area of the Puskesmas Tempiral in 2021.The conclusion in this study is that there are isit the relationship of knowledge and behavior toward the prevention of the transmission of leprosy in the work area of the Puskesmas Tempiral in 2021